Economic Complexity, Environmental Sustainability, and Technological Integration in Saudi Arabia: Analyzing Long-Term Trends - Abid, Ihsen; Gafsi, Nesrine (International Journal of Energy Economics and Policy, 2025)
The purpose of this research paper is to examine the long-term dynamics between economic growth, technological integration, and environmental sustainability in Saudi Arabia from 1995 to 2023. It aims to identify the impact of key economic, technological, and environmental indicators, including GDP, ICT sector performance, foreign direct investment (FDI), trade, and ecological footprint, on the country’s development trajectory. The research employs a quantitative approach, using VAR-VECM models to analyze time-series data. The study applies Granger causality tests and impulse response functions (IRFs) to investigate the causal relationships between variables, focusing on the effects of economic complexity (ECI), ICT, trade, FDI, and environmental sustainability. The findings reveal that economic growth, represented by GDP per capita, significantly impacts the ecological footprint over time, while trade plays a complex role in both environmental sustainability and economic diversification. Technological integration, especially through ICT exports, is closely linked to economic complexity, though foreign direct investment (FDI) appears to negatively influence the development of high-value sectors. The study also shows that while technological growth accelerates economic performance, it is accompanied by increased environmental impact, emphasizing the need for sustainable policies. The Granger causality tests indicate that the ecological footprint influences other variables, but its direct connection to GDP per capita is weak. This research contributes to the understanding of the interconnectedness between economic growth, technological development, and environmental sustainability in Saudi Arabia, providing insights for policymakers focused on achieving balanced, long-term growth. The study’s originality lies in its integration of various economic, technological, and environmental dimensions to analyze Saudi Arabia’s sustainable development trajectory, particularly through the lens of ICT and FDI.